7000 year-old tuberculosis cases from Hungary – Osteological and biomolecular evidence. (June 2015) - Masson, Muriel; Bereczki, Zsolt; Molnár, Erika; Donoghue, Helen D.; Minnikin, David E.; Lee, Oona Y.-C.; Wu, Houdini H.T.; Besra, Gurdyal S.; Bull, Ian D.; Pálfi, György
Summary: This study derives from the macroscopic analysis of a Late Neolithic population from Hungary. Remains were recovered from a tell settlement at Hódmezővásárhely-Gorzsa from graves within the settlement as well as pits, ditches, houses and as stray finds. One of the most important discoveries from these remains was evidence of tuberculosis. Pathological analysis of the seventy-one individuals revealed numerous cases of infections and non-specific stress indicators on juveniles and adults, metabolic diseases on juveniles, and evidence of trauma and mechanical changes on adults. Several cases showed potential signs of tuberculosis and further analyses were undertaken, including biomolecular studies. The five individuals were all very young adults and included a striking case of Hypertrophic Pulmonary Osteopathy (HPO) with rib changes, one case with resorptive lesions on the vertebrae, two cases with hypervascularisation on the vertebrae and periosteal remodelling on the ribs, and one case with abnormal blood vessel impressions and a possible lesion on the endocranial surface of the skull. The initial macroscopic diagnosis of these five cases was confirmed by lipid biomarker analyses, and three of them were corroborated by DNA analysis. At present, these 7000-year-old individuals are among the oldest palaeopathological and palaeomicrobiological cases of tuberculosis worldwide.